In the Light and in the Dark: Photocatalytic Fixation of Nitrogen into Ammonia and Nitrate at Iron Titanate Semiconductor Thin Films - Kisch, Horst (European Journal of Inorganic Chemistry, 2020)
This Minireview first summarizes the principle of semiconductor photocatalysis focusing on the comparability of photocatalytic activities, a central problem of the field, often leading to unjustified mechanistic conclusions. It then describes the visible light photofixation of pure and aerial nitrogen at a nanostructured Fe2Ti2O7 thin film on glass. In the presence of ethanol or humic acid, ammonia is formed via hydrazine in the photochemical, first reaction part. Since only reducing agents exhibiting a current amplification effect enable ammonia formation, it is proposed that the primary reduction of N-2 is a one-photon - two-electron proton-coupled electron transfer. A consecutive aerial oxidation of ammonia to nitrate constitutes the thermally catalyzed final reaction part, indicating the dual catalysis function of the film. Since the over-all reaction proceeds also with air, and weathering of corresponding iron titanium minerals could form Fe2Ti2O7 and similar semiconducting surfaces, a solar non-enzymatic nitrogen fixation by natural reducing agents may occur in nature. This aspect of environmental chemistry is largely unexplored.
CRIS-Team WoS Importer:2020-01-14